Factors influencing EFL learners’ speaking fluency: A case study at a high school in Vietnam - Tran, Du Thanh; Cao, Bich Thi Ngoc; Dang, Dung Thi Bao (Edelweiss Applied Science and Technology, 2024)
This study investigates how four key factors - English exposure, learning environment, motivation, and teaching pedagogy - affect English speaking fluency among high school students, using both qualitative and quantitative research methods. The findings indicate that frequent exposure to English, an engaging learning environment, and effective teaching pedagogy significantly enhance students’ speaking fluency and motivation. Qualitative results show that students who interact with English regularly, whether through classroom activities or extracurricular engagement, demonstrate better fluency and enthusiasm. A dynamic and supportive learning environment, combined with interactive teaching strategies, fosters higher levels of student participation and motivation. However, the study acknowledges several limitations. The small sample size used in the qualitative phase may not fully represent the broader student population, potentially impacting the generalizability of the findings. The reliance on self-reported data in the quantitative analysis introduces the possibility of bias, which could affect the accuracy of the results. The study also notes that focusing on a limited set of factors might overlook other influential elements such as individual learning styles or external pressures. Future research should aim to include a larger and more diverse sample, explore a broader range of factors affecting English fluency, and incorporate various activities and technological tools to address these limitations. By expanding the scope of research and incorporating these suggestions, more comprehensive strategies can be developed to improve English speaking fluency among students. This approach will provide valuable insights for educators and policymakers, assisting them in designing more effective language programs and interventions that enhance students’ communicative competence and overall language proficiency.